Eduard Gargallo and Jona Heita's transcript, Namibia, May 02, 2022 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2022)
Mentions to otjiherero and ovaherero use of languages and to the Owamboland region in the South West Africa territory To have access to the research data file, please contact: Eduard Gargallo egargallo@yahoo.com
Keywords: Arid regions; Tourism; Vaccination; Religious leaders; Mass media; Households; Community-based conservation; Livelihood; Conservancy; Drylands; Namibia; COVID-19 Pandemic